Implementasi Wireless Sensor Network Untuk Mendeteksi Gas Amonia Pada Kandang Ayam Menggunakan Modul Wifi ESP8266 - Mahdi Fiqia Hafis; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
We as Indonesian citizens feel proud of the high potential they have, especially in the field of animal husbandry and agriculture. With the existence of chicken farming, there are not a few who become new job creators and become independent in their work. The problem that is often experienced by chicken farmers is ammonia gas caused by chicken manure itself, this ammonia gas can later cause disruption in humans and also the chicken itself. Disorders in humans include respiratory problems, eye irritation, and poisoning in the form of seizures. The existence of internet of thing technology, can facilitate us in monitoring ammonia gas levels in the area of ​​chicken farms presented in the form of ppm by utilizing the mq-135 sensor that can detect ammonia gas levels. Data that has been taken by the client will be accommodated by the master and will be displayed on a web page with the help of a gateway to determine the level of ammonia gas in the area of ​​the chicken farm. The results of the study began with testing the quality of service to determine the performance of the network connection time for sending data to the server. And testing the function of a successful tool works perfectly where the mq-135 sensor can detect levels of dangerous gas ammonia (NH3).